Endovascular Intervention for Acute Ischemic Stroke in Light of Recent Trials - Kenan Alkhalili; Nohra Chalouhi; Stavropoula Tjoumakaris; David Hasan; Robert M. Starke; Mario Zanaty; Robert H. Rosenwasser; Pascal Jabbour (The Scientific World Journal)
Three recently published trials, MR RESCUE, IMS III, and SYNTHESIS Expansion, evaluating the efficacy and safety of endovascular treatment of acute ischemic stroke have generated concerns about the future of endovascular approach. However, the tremendous evolution that imaging and endovascular treatment modalities have undergone over the past several years has raised doubts about the validity of these trials. In this paper, we review the role of endovascular treatment strategies in acute ischemic stroke and discuss the limitations and shortcomings that prevent generalization of the findings of recent trials. We also provide our experience in endovascular treatment of acute ischemic stroke.